संस्कृतसाहित्यमञ्जरी, दशमश्रेणी - (:unkn) unknown (Board of Secondary Education Odisha, 2022)
The book is a prescribed Sanskrit textbook for class-10 by Odisha Board of Secondary Education.
Sanskruta Sahitya Manjari, Class-X
Keywords: Odia; संस्कृतसाहित्यमञ्जरी; दशमश्रेणी; Sanskruta Sahitya Manjari; Class-X; Sanskrit Literature; Odia; Odia